PENGARAUH MODEL PBL BERBANTUAN APLIKASI PLICKERS TERHDADAP HASIL BELAJAR SISWA PADA MATERI ORGAN TUBUH MANUSIA KELAS V SDN 55 PANGKALPINANG - Depita Kirana; Adi Saputra; Rifki Hanif Setiawan (STKIP Subang, 2026)
This study was conducted due to the still low learning outcomes of students. The purpose of this study is to understand the impact of using the Problem Based Learning (PBL) design supported by the Plickers application on students' learning outcomes in the topic of the human body organs in grade V students at SDN 55 Pangkalpinang. The study uses an experimental method with a pretest-posttest design. The sample of the study consists of grade VA with 27 students and grade VB with 28 students, using a saturated sampling technique. Data collection was conducted through multiple-choice tests in the IPAS subject. Data analysis included normality testing using the Shapiro-Wilk method and hypothesis testing using Liliefors. The results of the study show that the average pretest score in the experimental class was 34.4, while the control class had an average pretest score of 22.9. The average posttest score in the experimental class reached 92.8, while the control class had an average of 87.9. The hypothesis testing resulted in a significance value of 0.000, which is smaller than 0.05, thus Hₐ is accepted. Therefore, it can be concluded that the PBL model, supported by the Plickers application, has a significant effect on students' learning outcomes in the topic of the human body organs.